Tradisi Sedekah Tolak Bala pada Masyarakat Desa Langkan Kecamatan Banyuasin III Kabupaten Banyuasin (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2020)
Abstract Alms has various forms and virtues with abundant rewards both in this world and in the hereafter. Like the tradition of refusing bala in Langkan Village, alms that is done to reject reinforcements, both those that have not happened and those that have already happened, are by means of charity. For this reason, the formulation of the problem in this study is how the procedures for implementing alms to reject reinforcements in the Langkan Village community. What is the meaning of the tradition of rejecting bala for the people of Langkan Village and how is the relationship between the tradition of rejecting bala and hadith. The type of research is qualitative (field research), with a phenomenological approach. The object of this research is the tradition of alms-rejecting bala in the people of Langkan Village. The data sources were obtained from the people of Langkan Village with a purposive sampling technique and books related to research. Data collection techniques by means of observation, interviews and documentation. The data that has been collected is then described naturally and analyzed. The conclusion of this research is that the tradition of alms-rejecting bala is alms that is held both before a disaster and after a disaster, by asking Allah SWT to keep it away from reinforcements. The process of implementing alms to reject reinforcements is carried out by mutual cooperation, from preparation to implementation. By praying together and ending with a banquet. Then the meanings contained in the sedekah tradition of rejecting bala are a cultural result that cannot be separated from Islamic values. Like helping out, praying to God, strengthening brotherhood and friendship between family and society. The relation between the refusal of alms and the hadith of the Prophet SAW, as the Prophet Muhammad strongly advocated giving alms, because alms have many virtues, one of its virtues is to reject reinforcements. Rasulullah Saw not only recommended, but also carried out alms by giving something that was needed and useful. Keyword: Alms Tradition, Reject Bala, Langkan Village. Abstrak Sedekah memiliki berbagai bentuk dan keutamaan dengan pahala yang melimpah baik di dunia ini maupun di akhirat. Seperti tradisi menolak bala di Desa Langkan, sedekah yang dilakukan untuk menolak bala, baik yang belum terjadi maupun yang sudah terjadi, adalah dengan cara sedekah. Untuk itu rumusan masalah dalam penelitian ini adalah bagaimana tata cara pelaksanaan sedekah menolak bala pada masyarakat Desa Langkan. Apa makna tradisi menolak bala bagi masyarakat Desa Langkan dan bagaimana hubungan tradisi menolak bala dengan hadis. Jenis penelitiannya adalah kualitatif (penelitian lapangan), dengan pendekatan fenomenologi. Objek penelitian ini adalah tradisi menolak sedekah bala pada masyarakat Desa Langkan. Sumber data diperoleh dari masyarakat Desa Langkan dengan teknik purposive sampling dan buku-buku yang berkaitan dengan penelitian. Teknik pengumpulan data dengan cara observasi, wawancara dan dokumentasi. Data yang telah terkumpul kemudian dideskripsikan secara alami dan dianalisis. Kesimpulan dari penelitian ini adalah bahwa tradisi menolak zakat adalah sedekah yang dilakukan baik sebelum bencana maupun setelah bencana, dengan memohon kepada Allah SWT agar menjauhkannya dari bala bantuan. Proses pelaksanaan zakat tolak bala dilakukan secara gotong royong, mulai dari persiapan hingga pelaksanaan. Dengan berdoa bersama dan diakhiri dengan jamuan makan. Maka makna yang terkandung dalam tradisi sedekah menolak bala merupakan hasil budaya yang tidak lepas dari nilai-nilai Islam. Seperti membantu, berdoa kepada Tuhan, memperkuat persaudaraan dan persahabatan antara keluarga dan masyarakat. Kaitan antara penolakan sedekah dengan hadis Nabi SAW sebagaimana yang sangat dianjurkan oleh Nabi Muhammad adalah bersedekah, karena sedekah memiliki banyak keutamaan, salah satu keutamaannya adalah menolak bala. Rasulullah Saw tidak hanya menganjurkan, tetapi juga melakukan sedekah dengan memberikan sesuatu yang dibutuhkan dan bermanfaat. Kata Kunci: Tradisi Sedekah, Tolak Bala, Desa Langkan.